2009
DOI: 10.1097/ico.0b013e318181a84f
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab for the Treatment of Refractory Progressive Sterile Peripheral Ulcerative Keratitis Associated With Late Corneal Perforation: 3-Year Follow-Up

Abstract: Infliximab was effective in rapidly arresting the progression of a sterile PUK in our patient. Optimal dosing for infliximab in PUK has not been established, and increasing dose frequency to every 4 weeks may be necessary. Despite a progressive PUK resulting in corneal perforation, treatment with infliximab and subsequent visual rehabilitation can result in sustained remission and an excellent visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…[18][19][20] Odorcic et al in their study reported that there is not a recommended dose of infliximab in cases of peripheral ulcerative keratitis, and that reducing the interval between infusions to once every four weeks may be necessary. 4 Galor et al showed, in a study, stability in visual acuity in 68% of 12 patients with rheumatoid arthritis associated with peripheral ulcerative keratitis, following treatment with cyclophosphamide or methotrexate. 9 In the three cases here presented, we had favorable responses to infliximab in the treatment of ulcerative keratitis, prescribed after failure of corticosteroids and/or immunosuppressants, like other publications.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[18][19][20] Odorcic et al in their study reported that there is not a recommended dose of infliximab in cases of peripheral ulcerative keratitis, and that reducing the interval between infusions to once every four weeks may be necessary. 4 Galor et al showed, in a study, stability in visual acuity in 68% of 12 patients with rheumatoid arthritis associated with peripheral ulcerative keratitis, following treatment with cyclophosphamide or methotrexate. 9 In the three cases here presented, we had favorable responses to infliximab in the treatment of ulcerative keratitis, prescribed after failure of corticosteroids and/or immunosuppressants, like other publications.…”
Section: Discussionmentioning
confidence: 97%
“…9 Initially, the treatment consists of topical and systemic corticosteroids, such as prednisone at 1 mg/kg/day; this treatment might not be able to promote remission. 3,4,7 The use of immunosuppressants may be tempted, in view of the severity of the disease and the risk of vision loss. 14 Cyclophosphamide PO (2 mg/kg/day) or in monthly intravenous pulses may be used in conjunction with glucocorticoids in cases with risk of perforation or in the context of systemic vasculitides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infliximab therapy, which may cause gastrointestinal and hematological side effects, autoimmune diseases, hepatotoxicity and serious infections like tuberculosis, is now widely used in the treatment of RA, Crohn’s disease, ulcerative colitis, ankylosing spondylitis, plaque psoriasis and psoriatic arthritis. 14 Its ophthalmic use was first reported in 2001 for the treatment of panuveitis and RA-related scleritis. 15,16,17 Subsequent studies demonstrated the efficacy of systemic TNF-α blockers in the treatment of refractory ocular inflammatory diseases including refractory uveitis, scleritis and peripheral ulcerative keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,17 Subsequent studies demonstrated the efficacy of systemic TNF-α blockers in the treatment of refractory ocular inflammatory diseases including refractory uveitis, scleritis and peripheral ulcerative keratitis. 14,18,19 Also, intravenous or subcutaneous infliximab and etanercept have been used to treat SS patients, with conflicting results. 13,20,21 …”
Section: Discussionmentioning
confidence: 99%